Praktik Kawin Tangkap di Sumba Barat Daya dalam Perspektif Perkawinan Kristen - Malo, Marthen; Luji, Daud Saleh; Saingo, Yakobus Adi (KAMASEAN: Jurnal Teologi Kristen, 2023)
The aim of this paper is to examine marriage by capture from the perspective of Christian marriage so that, in the end, the church, government, and all levels of society can determine the correct attitude towards catch marriage. This paper uses a qualitative method with data collection techniques using observation, interviews, and documentation studies. Sampling used purposive sampling and snowball sampling. Capture marriage, one of the marriage methods in Sumba, East Nusa Tenggara, is a tradition of kidnapping women to make her a bride. This has been practiced by noble descendants for prestige purposes since the era of kingdom rule in Sumba. The results obtained show that marriage by capture has experienced a shift in meaning, where it was once done for prestige and by mutual consent, but now it is an act of violence and crime that is very detrimental and even demeaning to women. In the perspective of Christian marriage, the capture of marriage is an act that opposes the Word of God because marriage should be based on love. The government, churches, non-governmental organizations, traditional leaders, and community leaders have expressed their rejection of marriage by capture. Evidence of this rejection is the existence of policies or regulations and a number of other programs to overcome and eliminate capture marriage. However, so far, the government, churches, non-governmental organizations, traditional leaders, and community leaders have not really implemented every existing regulation.